Competition in the growth period of partnership supply networks based on multi-joint distribution and virtual alliance: A sustainable approach. (September 2021) - Rezaei, S.; Behnamian, J.
Graphical abstract: Highlights: A competitive supply network is established to achieve partnership-based mechanisms. The aim is to establish exclusive relationships among major manufacturer and parent. The franchise strategy at the downstream level of supply network is developed. The virtual alliance among members and multi-agent transshipment are utilized. Two competitive algorithms based on game theory concepts and a model are developed. Abstract: Supply chain networks developed upon the classical exclusive ownerships are to a great extent vulnerable and penetrable. The rapid pace of change in today's globalization has made it impossible for a centralized operation to succeed in all aspects of performance. To keep up with demands in this situation, this paper proposes an approach wherein supply networks, with independent ownerships of resources, compete against each other to maximize their market share. This competition is carried out in the growth phase of supply networks which are relationship-based managed under main firms' brands. In this study, environmental sustainability is achieved through the development of a multi-agent (multi-network) distribution mechanism. Although several studies have been conducted in multi-factory manufacturing, this paper is the first attempt to develop such an environmentally sustainable shared platform in the distribution level of the network (including main firms (brands), manufacturers, governmental logistics service providers, and franchised retailers). Even more striking, the downstream members of the network (franchised stores) are to increase their monopoly interests alongside attempting to expand the overall share of the main brand. This implies a left-behind concept called virtual alliance. This problem is formulated using a mixed-integer programming model. Further, two gaming-based heuristic algorithms are prepared in the Nash and Stackelberg formulations. To evaluate the efficiency of the chosen scheme, a real-world example is considered and compared with a classical case. The obtained results illustrate a better performance of the proposed approach.